Nilai-Nilai Akhlak, Agama, dan Kemanusiaan dalam Novel Ayat-Ayat Cinta 2 Karya Habiburrahman El-Shirazy - Huda, Nurul Afiatul; Sumadi, Sumadi; Selamet, Selamet (Bestari | Jurnal Studi Pendidikan Islam, 2020)
This research discusses the moral values ​​of religion and fellow humans in the novel Ayat-ayat Cinta 2 by Habiburrahman El-Shirazy. The research method used is library research, namely a series of activities related to the method of collecting library data, reading and taking notes and processing research materials. The results of research and discussion conducted by researchers in conducting this research are reading, analyzing and searching for sources With regard to data that is in accordance with the moral values ​​in the novel ayat-ayat-cinta, after which the author obtains some moral values ​​contained in the Novel Ayat-ayat Cinta 2. After analyzing the data, the following conclusions are obtained: (1) Moral values ​​for religion contained in the Novel Ayat-ayat Cinta 2 by Habiburrahman El-Shiazy include worship, monotheism of Allah, gratitude, dzikir, fear of Allah SWT. (2) Moral values ​​towards fellow human beings include patience, trustworthiness, tawadhu, hard work and discipline, sincerity, living simply, doing good to parents and family, helping out, respecting guests and advising each other.